THE CORRELATION BETWEEN THE READING HABIT OF THE 10TH GRADE STUDENTS OF SMK ABDURRAB PEKANBARU AND THEIR READING COMPREHENSION ABILITY IN RECOUNT TEXTS (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this discussion was to perceive the correlation between Reading Habit and Reading Comprehension in Recount Text of 10th grade students of SMK Abdurrab Pekanbaru. Low ability to understanding of students to understand was the based on the background the problem of the research and capture the information contained in complex reading texts. And students have reading habits and reading speed is quite low. This makes the researcher is interested discover the interrelation between reading habits and students' reading comprehension abilities. The purpose of this research is to see the extent of the connection between reading habits and students' reading comprehension abilities. Researcher used cluster sampling because the object of research is broad. The research instrument is a reading test and a questionnaire about reading habits. The researcher used the validity test calculated with the SPSS 21 program with the tried-out method, then compared the r-count and r-table and it was found that the instruments of both variables were valid. As well as the reliability test with the results of 0.909 and 0.920 for the two variables in the very reliable category. This research result discovered significance value is 0.627, which was obtained through the SPSS 21 program. With this, it can be concluded that 0.607 > 0.05, which means that there is no effect of reading habit on reading comprehension ability. While the results of the linear regression analysis obtained the formulation Y= 28,824 + 0.203X. Because the regression coefficient value showed a positive value, it can be concluded that reading habit (X) has a positive effect on students' reading comprehension ability (Y). To see how much influence the two variables have, it can be seen from the R-Square value through the SPSS output, which is 0.014 which means that the influence of reading habit on students' reading comprehension ability is 1.4%, while 98.6% is influenced by other variables outside of this study, so it can be concluded that reading habit has a very low influence on students' reading comprehension ability, which means Ho is acquired and Ha is declined in this study.Key Words: Reading Habit, Reading Comprehension, Recount Text